ORGANA BIOTECH AS A CASE STUDY OF THE USE OF GRAVIMETRY AS AN EFFECTIVE METHODOLOGY FOR MEASURING AND REDUCING ORGANIC WASTE - Novais da Silva, Fernando; immermann, Guilherme Z (Revista Gênero e Interdisciplinaridade, 2025)
Reducing food waste is a global priority established by Sustainable Development Goal (SDG) 12.3. Accurate measurement of food residues is essential to support public policies and mitigation strategies. In this context, gravimetry emerges as a reliable methodology for quantifying waste, providing objective and comparable data. This article analyzes the applicability of gravimetry as a diagnostic and monitoring tool, highlighting its advantages, limitations, and practical applications across different institutional settings. As an illustrative case, the study examines Organa Biotech, a company that employs gravimetry as an effective method for measuring and reducing organic waste. This research was supported by the Fundação de Amparo à Pesquisa e Inovação do Estado de Santa Catarina (FAPESC), through Public Call No. 50/2024 – Programa Impulsiona SC.